2010
DOI: 10.1080/10888700903369255
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Relinquished Dogs and Their Owners at 14 Rehoming Centers in the United Kingdom

Abstract: In the United Kingdom, each year many companion animal (pet) caregivers (owners) hand over dogs to shelters for rehoming. Studies conducted in the United States and Australia have shown that accommodation issues and problematic behaviors are the most common reasons for dogs to be relinquished. The purpose of this study was to provide a clearer understanding of common characteristics of relinquished dogs in the United Kingdom. A descriptive study conducted during 2005 collected data on 2,806 dogs relinquished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 19 publications
3
92
0
Order By: Relevance
“…Therefore, a careful selection and education of the new owners is highly recommended [2]. Although no studies exist that tested these recommendations for laboratory beagles, Diesel et al [28, 40] confirmed their usefulness based on their experience with shelter dogs. Gazzano et al [41] showed that a 1-hour counseling of puppy owners reduced the occurrence of subsequent behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a careful selection and education of the new owners is highly recommended [2]. Although no studies exist that tested these recommendations for laboratory beagles, Diesel et al [28, 40] confirmed their usefulness based on their experience with shelter dogs. Gazzano et al [41] showed that a 1-hour counseling of puppy owners reduced the occurrence of subsequent behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that animals obtained at low or no cost are at increased risk of relinquishment, presumably because they may represent a less committed purchase [12]. Behavioural problems have been shown to increase the risk of relinquishment [29], and relinquishing owners have been shown to be relatively poorly informed on basic behaviour. For example, in one study >50% of relinquishing cat and dog owners thought that their animals misbehaved 'out of spite' [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted sex differences for the number of dogs and cats being relinquished to centers (Diesel, Brodbelt, & Pfeiffer, 2010;Lepper, Kass, & Hart, 2002;Salman et al, 1998), and Ulfsdotter et al (2016) also reported a 5.1% difference in the number of male and female rabbits being relinquished through online advertisements in Sweden, with more males being relinquished. Similar to the findings of Ulfsdotter et al,4.8% more male rabbits were relinquished in the present study.…”
Section: Rabbit Factorsmentioning
confidence: 95%